Implementasi Pembinaan Program Forum Komunikasi UMKM terhadap Kinerja Pelaku UMKM di Kelurahan Bantarjati, Kota Bogor - Amiruddin Saleh; R.Ng Handhoyo (Jurnal Komunikasi Pembangunan, 2017)
MSME’s in Indonesia are increasingly important in the process of national economic development in Indonesia. The MSME’s institution is considered an important source of job creation and the main driving force of regional economic development in Indonesia. With regard to poverty reduction and unemployment policies, the government continues to commit to building and empowering MSME’s in Indonesia. Improving the work of the perpetrators can be seen after the evaluation of the guidance program MSME’s actors. Implementation of MSME’s development program in forming an ideal MSEE practice is influenced by input, process and output of MSME’s program development. The input factor is measured from the individual characteristics of SME actors, the majority are in the middle adult age, the education is dominated by the SMA level, the average business actor runs less than 10 years and the majority only once training, the process factor is measured from the MSME’s development program; capital assistance including high class, low partnership development, high training and promotion of SME’s in  the moderate class while the output factor is seen from the performance of SME’s actors; income levels are moderate, increasing the number of medium consumers, low competition level and low product selling power. The research method used is quantitative research, namely the use of instruments in the form of questionnaires and supported qualitative data obtained through in-depth interviews. The result of the research shows that there is no real correlation between individual characteristic and coaching program, beside that individual characteristic also have no correlation with performance of MSME’s actor only at educational level indicator with sales level having relationship, while coaching program has influence with performance improvement of MSME’s actors , it is necessary to evaluate the coaching program so that the future of this program get maximum results in accordance with the government's goal for improvement on the perpetrators of MSME’s.